Research on the mechanisms of contact resistance and structural deformation impact on PEMFC performance - Teng Ma; Guoxi Jing; Chengbo Hu; Yanzhou Qin; Xiuxiu Sun (Case Studies in Thermal Engineering)
The manufacturing and assembly processes of proton exchange membrane fuel cells (PEMFCs) are associated with certain challenges. The clamping force exerted during the assembly process plays a crucial role in the functioning of the PEMFCs. The associated mechanisms are complicated and remain unexplored. Hence, this study investigated the mechanisms whereby the clamping force influences the PEMFC in terms of the structural deformation of the membrane electrode assembly, electrical contact resistance, and thermal contact resistance (TCR). Considering the influence of the clamping force on reactant flow, the ideal compression level was identified to be 1 MPa for optimum PEMFC performance, electron transfer, hydrothermal management, and reaction inhomogeneity. Applying this clamping force during the assembly of a single cell into a stack can produce a good thermal distribution uniformity. Meanwhile, the TCR significantly affected the thermal transfer in the through-plane direction and the hydration effect of the membrane in the cell. The TCR exhibited a 1 %–5 % impact on the cell performance, which is considered non-negligible in the development of PEMFCs. Our findings can aid the manufacturing of PEMFCs from the standpoints of effective thermal management and reaction completion.